Absorption and Excretion of 3-Chloromercuri-2-Methoxypropylurea Labeled with Hg203 - Anghileri, Leopoldo José (Nuklearmedizin - NuclearMedicine, 1964)
A method of preparation of Hg203-labelled 3-chloromercuri-2-methoxypropylurea is given. At the same time the solvent to be used in the chromatographic assay of its radioactive purity is indicated.The absorption and excretion of this compound was studied in rats.A maximum of activity was observed in the kidneys during the first six hours. Subsequently the activity in the kidneys decreased whereas it increased in the intestine. After the first week, the biological half life for the whole body was 8 days and for the kidneys approximately 28 days.A high percentage of the activity in the kidneys was ionic mercury.On décrit une méthode de préparation du 3-chloromercuri-2-methoxypropylurea-Hg-203. On indique à la fois, le solvant à employer dans la Chromatographie d’après l’exigence de sa pureté radioactive.On étudie la distribution et l’excrétion de ce composé avec des rats.Les reins présentent un maximum d’activité dans les premières six heures, en décroissant après à la fois qu’elle augmente à l’intestin.Après la première semaine, la vie moyenne biologique pour tout le corps est de 8 jours tandis que pour les reins c’est à peu près de 28 jours.Dans les reins on retrouve alors un pourcentage élevé de Hg-203 à l’état ionique.Eine Methode für die Herstellung von 3-Chloromercuri-2-methoxypropylurea Hg-203 wurde angegeben.Zur gleichen Zeit wurde die Lösung genannt, die in der chromatographischen Analyse der radioaktiven Reinheit gebraucht wird.Die Resorption und die Ausscheidung dieser Zusammensetzung wurde an Ratten versucht.Ein Maximum an Aktivität wurde in den Nieren während der ersten sechs Stunden beobachtet. Später nahm die Aktivität in den Nieren ab, während sie in den Därmen zunahm.Nach der ersten Woche ist die biologische Halbwertzeit für den ganzen Körper 8 Tage und für die Nieren durchschnittlich 28 Tage.Ein großer Prozentsatz der Aktivität in den Nieren war ionisiertes Quecksilber.